2021
DOI: 10.1093/nop/npab026
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Treating Fields for the treatment of glioblastoma: a systematic review and meta-analysis

Abstract: Background Tumor-Treating Fields (TTFields) is an emerging treatment modality for glioblastoma (GBM). Studies have shown a good safety profile alongside improved efficacy in newly diagnosed GBM (ndGBM), while a less clear effect was shown for recurrent GBM (rGBM). Despite regulatory support, sectors of the neuro-oncology community have been reluctant to accept it as part of the standard treatment protocol. To establish an objective understanding of TTFields' mechanism of action, safety, effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 93 publications
0
12
0
1
Order By: Relevance
“…The EF-14 trial was an open-label, non-sham-controlled randomized phase III trial investigating the addition of TTF to standard therapy and demonstrated an improvement in median OS (20.9 versus 16 months) and PFS (6.7 versus 4 months) without compromising the health-related quality of life (HRQoL) [ 79 81 ]. However, compliance with TTF might be a limiting factor for its implementation in real-world practice [ 82 ]. A sub-group analysis from the same trial [ 83 ] has shown that the minimum average compliance rate threshold is 50% for a clinical gain in PFS (HR 0.70, 95% CI 0.47–1.05) and OS (HR 0.67, 95% CI 0.45–0.99) to be attained with a stepwise increase in both outcomes with higher compliance rates.…”
Section: Current Approach To Newly Diagnosed Gbmmentioning
confidence: 99%
“…The EF-14 trial was an open-label, non-sham-controlled randomized phase III trial investigating the addition of TTF to standard therapy and demonstrated an improvement in median OS (20.9 versus 16 months) and PFS (6.7 versus 4 months) without compromising the health-related quality of life (HRQoL) [ 79 81 ]. However, compliance with TTF might be a limiting factor for its implementation in real-world practice [ 82 ]. A sub-group analysis from the same trial [ 83 ] has shown that the minimum average compliance rate threshold is 50% for a clinical gain in PFS (HR 0.70, 95% CI 0.47–1.05) and OS (HR 0.67, 95% CI 0.45–0.99) to be attained with a stepwise increase in both outcomes with higher compliance rates.…”
Section: Current Approach To Newly Diagnosed Gbmmentioning
confidence: 99%
“…Tumor-Treating Fields (TTFields) are emerging radiation treatment modalities for GBM, which has shown a good safety profile and better efficacy in newly diagnosed GBM, while a less clear effect was shown for recurrent GBM [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…FFF beams allow up to a four-fold increase in the dose rate, thus reducing the probability of the patient’s motion and increasing his comfort. At state of the art, FFF is a technique already experienced in clinical settings in Stereotactic Body Radiation Therapy (SBRT) of vertebral, lung, liver, or intracranial tumors [ 3 ] thanks to the generated high gradient dose distribution hence the benefit of limiting normal tissue damage while preserving the tumor control rate.…”
Section: Introductionmentioning
confidence: 99%
“…Рецидив пов'язаний з майже універсальною смертністю. Медіанна виживаність після рецидиву становить від 9 до 20 міс [6][7][8] залежно від стратегії лікування.…”
unclassified